Meta-Analysis With a Continuous Covariate That Is Differentially Categorized Across Studies - Perin, Jamie; Fischer Walker, Christa L; Black, Robert E; Aryee, Martin J (American journal of epidemiology, 2016)
We propose taking advantage of methodology for missing data to estimate relationships and adjust outcomes in a meta-analysis where a continuous covariate is differentially categorized across studies. The proposed method incorporates all available data in an implementation of the expectation-maximization algorithm. We use simulations to demonstrate that the proposed method eliminates bias that would arise by ignoring a covariate and generalizes the meta-analytical approach for incorporating covariates that are not uniformly categorized. The proposed method is illustrated in an application for estimating diarrhea incidence in children aged ≤59 months.